A Note on Blending of Pulps from Eucalptus hybrid and Saw-mill Waste of Conifers - Sharma, Y. K.; Dhawan, Rita; Karira, B. G. (Indian Forester, 1983)
Airy Shaw while describing Gentianella glanduligera in 1943 stated that it was unknown in wild state. Recently, however, it has been collected in wild state in India and is being reduced to a varietal rank under Gentianella maddenii (Clarke) Airy Shaw. T. A. Rao collected a specimen in 1957 from Kumaun Hills and identified it as Gentiana recurvata Clarke; it was recorded by him as new for the North-West Himalaya. A critical study of this specimen revealed that it actually belonged to Gentianella glanduligera Airy Shaw having smaller stems and flowers than the Gentianella maddenii (Clarke) Airy Shaw; protologue and icon of the species confirmed the identity.